Contribution of Islamic Worldview to Leadership and Student Learning Outcomes - Sarwo Edy (Al-Hayat: Journal of Islamic Education, 2022)
Schools must be managed healthily and effectively for noble purposes, so people must lead schools with reliable leadership capacity and good integrity. Several studies have stated that the effectiveness of Islamic school management rests on its human resources, which are capable and must have the competence and integrity of a pious personality. From this conception, it is necessary to know how essential school leaders are. This study aims to determine the contribution of the Islamic worldview to school leadership and student learning outcomes. The research design used a survey and was ex post facto conducted on a sample of 154 from 38 districts/cities of Muhammadiyah Elementary School Principals using an area random sampling technique. From these data, it can be concluded that the Islamic worldview presented to the principal affects his leadership practice in Islamic elementary schools. At the same time, the student learning outcomes are indirect through the rational path – organizational and emotional path. It was found that the Islamic worldview factor, which theoretically covers human behaviour, has been shown to strongly contribute to the principal's leadership behaviour and teacher behaviour.